Photovoltaic and impedance spectroscopy analysis of p-n like junction for dye sensitized solar cell - Yahia, I. S.; Hafez, Hoda S.; Yakuphanoğlu, Fahrettin; Senkal, B. Filiz; Mottaleb, M. S. A. Abdel (Elsevier Science Sa, 2011)
A dye-sensitized solar cell based on nanostructure TiO(2) and PCBM:P3HT blend was fabricated and the photovoltaic and impedance spectroscopy properties of the solar cell were investigated. The solar cell gives a short circuit current density of 0.75 mA/cm(2) and an open circuit voltage of 0.60 V under AM1.5. The photovoltage of the solar cell was greatly enhanced by PCBM:P3HT blend. The capacitance-voltage, the conductance-voltage, the series resistances-voltage characteristics of the solar cell were measured in a wide range of frequency for the first time for DSSC applications. The capacitance-voltage shows a behavior from the positive to negative capacitance due to injection of electrons from the FTO electrode into TiO(2). It is evaluated that the photovoltaic performance of the dye-sensitized solar cell can be improved using various organic semiconductors. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: TiO(2) nanostructure; PCBM:P3HT; Photovoltaic properties; Impedance spectroscopy; Positive and negative capacitance